ESMAT: online smart zakat counter for integrated zakat management system / Naimah Zaini ... [et al.] - Zaini, Naimah; Omar, Nor Bahiyah; Arshad, Roshayani; Muda, Ruhaini (2020)
COVID-19 pandemic has not only affected lives but also had a strong impact on various sectors including education sector. The needs to self-isolated at home has impacted students especially from B40 families. They are not able to apply zakat using a normal procedure as in the campus and hence, affects their quality of online distance learning (ODL) process. Although most of the higher education in Malaysia have a specific unit or department which handle the collection and distribution of zakat in their institutions, some of the institutions still manage and distribute zakat manually. As such, tedious process involved where students have to download and fill form and submitted directly to Islamic Affairs Religious Unit (UHEI) which will be processed and later be interviewed by the Zakat Unit Officer. Students then have to wait for the information from UHEI on their application status. With a new norm where students have to practice social distance and not necessary to be in the campus, it is believed that developing an ESMAT which simplify the application and distribution process of zakat to students will improve the effectiveness of zakat management. ESMAT will provide an opportunity for UHEI to be more transparent about their zakat distribution and enhance their trust to zakat payers and society as whole.